2023
DOI: 10.1161/circresaha.122.321636
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia-Induced Inflammation, Resolution and Cardiovascular Disease: Causes, Consequences and Clinical Opportunities

Abstract: Pneumonia is inflammation in the lungs, which is usually caused by an infection. The symptoms of pneumonia can vary from mild to life-threatening, where severe illness is often observed in vulnerable populations like children, older adults, and those with preexisting health conditions. Vaccines have greatly reduced the burden of some of the most common causes of pneumonia, and the use of antimicrobials has greatly improved the survival to this infection. However, pneumonia survivors do not return to their prei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 291 publications
0
5
0
1
Order By: Relevance
“…The immune response to CAP is a complex process of innate and adaptive immunity mediated by pro-inflammatory responses, endothelial activation, and pneumonia resolution mediated by anti-inflammatory responses ( 2 , 26 , 27 ). Preclinical in vitro and in vivo studies have shown that acute hyperglycaemia induces proinflammatory cytokine and chemokine responses and endothelial activation ( 28 30 ), while type 2 diabetes is associated with dysregulated immune responses and endothelial dysfunction ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to CAP is a complex process of innate and adaptive immunity mediated by pro-inflammatory responses, endothelial activation, and pneumonia resolution mediated by anti-inflammatory responses ( 2 , 26 , 27 ). Preclinical in vitro and in vivo studies have shown that acute hyperglycaemia induces proinflammatory cytokine and chemokine responses and endothelial activation ( 28 30 ), while type 2 diabetes is associated with dysregulated immune responses and endothelial dysfunction ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the literature reporting that histopathologic damage in lung tissue is associated with oxidant/antioxidant levels 49,50 . Pneumonia is a widely recognized condition characterized by inflammation of the lungs, typically due to an infection 51 . There is currently no information available in the litera-ture suggesting that favipiravir induces interstitial inflammation via oxidative stress in the lungs.…”
Section: Footnotesmentioning
confidence: 99%
“…Similarly, pneumococcal infection induces oxidative stress and triggers inflammatory markers that can lead to thrombogenesis (formation of blood clots), destabilization of atherosclerotic plaques (hardening or narrowing of arteries due to plaque buildup), and endothelial dysfunction. Consequently, pneumococcal infections amplify the likelihood of developing HF 22 .…”
Section: Reviewmentioning
confidence: 99%